Knowledge about sexually transmitted infections does not associate with attitude towards LGBT behavior - Munadiah Jannatun Naimah; Baksono Winardi; Pudji Lestari (Universitas Airlangga, 2020)
Objective: To analyze the association between knowledge about sexually transmitted infections and attitudes towards LGBT behavior in teenagers at Trimurti High School Surabaya. Materials and Methods: A cross sectional study with a sample of 96 students who were selected by random sampling technique based on the attendance list. The data was collected by using primary data via questionnaires at Trimurti High School students in the academic year of 2017/2018. Data were analyzed using Chi Square test. Results: 56.3% of respondents had sufficient knowledge about sexually transmitted infections, 56.3% of respondents had a positive attitude towards LGBT behavior. Chi Square test in significance level of 0,05 reveal p value equal to 0,582, indicating there is no association between the level of knowledge about sexually transmitted infections with attitudes towards LGBT behavior in teenagers at Trimurti High School Surabaya. Conclusion: There is no association between the level of knowledge about sexually transmitted infections and attitudes towards LGBT behavior in teenagers at Trimurti Surabaya High School.